Cover, Content, and Editorial Note from Borneo J Pharm Vol. 8 No. 2 May 2025 - Borneo J Pharm, Chief Editor of (Borneo Journal of Pharmacy, 2025)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm) has been published in May 2025. This edition contains ten articles: Pharmacology-Toxicology, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, and Natural Product Development. This edition includes writings from two countries: Indonesia and Thailand. The authors come from several institutions, including Universitas Sari Mulia, Universitas Borneo Lestari, Universitas Ahmad Dahlan, Sekolah Tinggi Ilmu Kesehatan Samarinda, Universitas Alma Ata, Universitas Jambi, Universitas Bengkulu, Universitas Muhammadiyah Prof Dr Hamka, Institut Teknologi Bandung, Universitas Halu Oleo, Thammasat University, Universitas Jember, Universitas Airlangga, Universitas Anwar Medika, Universitas Muhammadiyah Kalimantan Timur, and Universitas Muhammadiyah A.R. Fachruddin. Editorial boards are fully aware that there is still room for improvement in this edition; hence, with all humility, we are willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors, reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors, could re-participate in the publication in the next edition in August 2025. Wassalamu’alaikum Wr. Wb.